Identification of an HIV-1 BG Intersubtype Recombinant Form (CRF73_BG), Partially Related to CRF14_BG, Which Is Circulating in Portugal and Spain - Fernández-García, Aurora (PLoS One, 2016)
HIV-1 exhibits a characteristically high genetic diversity, with the M group, responsible for the pandemic, being classified into nine subtypes, 72 circulating recombinant forms (CRFs) and numerous unique recombinant forms (URFs). Here we characterize the near full-length genome sequence of an HIV-1 BG intersubtype recombinant virus (X3208) collected in Galicia (Northwest Spain) which exhibits a mosaic structure coincident with that of a previously characterized BG recombinant virus (9601_01), collected in Germany and epidemiologically linked to Portugal, and different from currently defined CRFs. Similar recombination patterns were found in partial genome sequences from three other BG recombinant viruses, one newly derived, from a virus collected in Spain, and two retrieved from databases, collected in France and Portugal, respectively. Breakpoint coincidence and clustering in phylogenetic trees of these epidemiologically-unlinked viruses allow to define a new HIV-1 CRF (CRF73_BG). CRF73_BG shares one breakpoint in the envelope with CRF14_BG, which circulates in Portugal and Spain, and groups with it in a subtype B envelope fragment, but the greatest part of its genome does not appear to derive from CRF14_BG, although both CRFs share as parental strain the subtype G variant circulating in the Iberian Peninsula. Phylogenetic clustering of partial pol and env segments from viruses collected in Portugal and Spain with X3208 and 9691_01 indicates that CRF73_BG is circulating in both countries, with proportions of around 2–3% Portuguese database HIV-1 isolates clustering with CRF73_BG. The fact that an HIV-1 recombinant virus characterized ten years ago as a URF has been shown to represent a CRF suggests that the number of HIV-1 CRFs may be much greater than currently known.